TOXICITY OF SAN LUIS POTOSIRAY OILS TO IMMATURE FORMS OF THE CITRUS BLACKFLY - SHAW, JG; PLUMMER, CC (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1976)
Protected branches of sour lime trees with eggs of Aleurocanthus woglumi on the leaves were sprayed with emulsions, 083, 125, and 167% of light, light-medium, and medium emulsive spray oils in water, and also with 167% light-medium oil containing 45
J GEN MICROBIOL
Keywords: TOXICITY, SPRAY OILS, IMMATURE FORMS, CITRUS BLACKFLY; CIENCIAS DE LA VIDA; BIOLOGIA DE INSECTOS; ENTOMOLOGIA GENERAL